Spectral and chromatographic characterisation of the onoceroid, ambrane: A potential novel biological marker. (December 2016) - Sutton, Paul A.; Rowland, Steven J.
Abstract: The gas chromatography–mass spectrometry (GC–MS) characteristics, including GC retention indices and mass spectra, of isomers of the tricyclic onoceroid C30 hydrocarbon, ambrane (1, 1, 4a, 6-tetramethyl-5-{4-methyl-6-[2, 2, 6-trimethylcyclohexyl]hexyl}decahydronaphthalene) are reported. Ambrane is yet to be reported in sediments or petroleum: other biochemically-related onoceroids, such as onoceranes and serratanes, have been. Now that GC–MS data are available, a search for ambranes in geochemical samples may be both feasible and warranted.